Konsepsi Kosmologi dalam Pengobatan Usada Taru Pramana - I. G. P Suryadarma (Journal of Tropical Ethnobiology, 2005)
Usada Tani Pramana (usada) is one of an ancient traditional medicine script that was written in palm leaves, lontar (Borrasus in Bali language on 11th century. Usada knowledge unique is being pushed by modern treatment speciality and need knowledge innovation also plants protection at Tri Mandala landscape of Bali society. The objectives of this research are (1) to analyse content of usada knowledge, (2) to study the people knowledge about number of plant species, and (3) to identify plants distribution at Tri Mandala village. The result of study shows that Usada Thru Pramana script has unity of treatment information by various plants selection therapy. It was documented 14 disease groups and 161 plants species that 70 % of them is used in modern treatment ; Societies knowledge is enough and old generation knowledge is better as their experience in using haracaraka letter such of using in usada. There is degradation in listening experience, seeing, using for medicine because of script limitation and oral heritance ; The plants species of usada is distributed in equally at Tri Mandala village zone where accumulative amount is 149 species.